1999
DOI: 10.1210/jcem.84.3.5535
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Low Dose Short Synacthen Test (1 μg), the Conventional Dose Short Synacthen Test (250 μg), and the Insulin Tolerance Test for Assessment of the Hypothalamo-Pituitary-Adrenal Axis in Patients with Pituitary Disease

Abstract: There is still uncertainty about what is the most appropriate test for assessment of the integrity of the hypothalamo-pituitary-adrenal (HPA) axis. Many advocate the insulin tolerance test (ITT), but this is unpleasant and resource intensive, and may occasionally give misleading results. The conventional [250 microg tetracosactrin, ACTH-(1-24)] short synacthen test (SST) has been used as a simple alternative to the ITT, but it has produced some falsely reassuring results with potentially serious consequences. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(110 citation statements)
references
References 0 publications
5
104
0
1
Order By: Relevance
“…7,13 The adrenocorticotropin stimulation test is used to evaluate adrenal cortisol production. The standard-dose ACTH stimulation test (250 mg cosyntropin) is typically used to diagnose primary adrenal insufficiency, while the low-dose ACTH stimulation test (1 mg cosyntropin) is more sensitive than the standard-dose test [14][15][16][17] and thus may be more appropriate for diagnosis of subtle adrenal insufficiency, including secondary adrenal insufficiency or adrenal suppression, to test for adrenal recovery. A peak cortisol response 420 mg per 100 ml is generally considered normal, and 18-20 mg per 100 ml is considered borderline.…”
Section: Discussionmentioning
confidence: 99%
“…7,13 The adrenocorticotropin stimulation test is used to evaluate adrenal cortisol production. The standard-dose ACTH stimulation test (250 mg cosyntropin) is typically used to diagnose primary adrenal insufficiency, while the low-dose ACTH stimulation test (1 mg cosyntropin) is more sensitive than the standard-dose test [14][15][16][17] and thus may be more appropriate for diagnosis of subtle adrenal insufficiency, including secondary adrenal insufficiency or adrenal suppression, to test for adrenal recovery. A peak cortisol response 420 mg per 100 ml is generally considered normal, and 18-20 mg per 100 ml is considered borderline.…”
Section: Discussionmentioning
confidence: 99%
“…60,71,86 -91 The majority of these divergent responses occur in patients who show poststimulation cortisol values of between 500 and 650 nmol/L. 92,93 In one recent study of 148 patients at risk of developing secondary adrenal insufficiency due to cranial irradiation, pituitary surgery or concomitant glucocorticoid therapy, only one patient with a normal synacthen response (30 min cortisol .550 nmol/L) and one patient with a borderline result (510-550 nmol/L at 30 min) developed clinical adrenal insufficiency. 94 Based on these observations, the false-negative rate for the synacthen test is ,1%.…”
Section: Synacthen and Ittsmentioning
confidence: 99%
“…Furthermore, as the ITT is not 100% sensitive, there may be infrequent patients who pass the ITT but who are later found to have adrenal insufficiency. 76,93 A study of patients following pituitary surgery found six of a group of 41 who failed the low-dose (1 mg) synacthen test one week after surgery subsequently passed the ITT at 4 -6 weeks postsurgery. 75 In contrast, three of 40 patients had a normal response to the standard-dose synacthen test but a subnormal response to the ITT.…”
Section: Synacthen and Ittsmentioning
confidence: 99%
“…20,21 It is prepared by diluting the 250-μg vial in 250 ml of normal saline to obtain a concentration of corticotrophin (ACTH) 1 mcg/ml and using a 1-ml syringe to accurately draw a dose. The syringes can be kept at 4°C for up to 4 months without any decline in biologic activity 22 .…”
Section: Low Dose (1 Mcg) Testmentioning
confidence: 99%